A pragmatic multi-setting healthy lifestyle intervention to improve BMI status in a middle-income population: A potential strategy for individuals at risk - Reza Yari-Boroujeni; Leila Cheraghi; Parnian Parvin; Fatemeh Shiravi; Hasti Masihay-Akbar; Amirabbas Momenan; Arash Ghanbarian; Parvin Mirmiran; Davood Khalili; Fereidoun Azizi; Parisa Amiri (Health Promotion Perspectives)
Background: To evaluate a multi-setting lifestyle intervention’s effect on body mass index (BMI) across the entire spectrum in a middle-income adult population over 15 years. Methods: This pragmatic interventional study included 5153 adults (≥20 years) from a middle-income community, followed for over 15 years with five follow-ups. A multi-setting intervention (school, family, community) aimed to promote healthy lifestyles. The lambda-mu sigma (LMS) method and quantile regression model were used to analyze changes in BMI percentiles (10th-90th) by sex and intervention group. Results: The intervention showed modest effects on BMI percentiles. In men, it lowered BMI at the 40th and 70th percentiles (overweight/obesity onset) at the first follow-up (β=-0.16, 95% CI: -0.33, -0.001 and β=-0.21, 95% CI: -0.38, -0.04 respectively). In women, the effect emerged later (second follow-up) at the 20th (β=-0.39, 95% CI: -0.60, -0.18), 30th (β=-0.27, 95% CI: -0.49, -0.04), and 60th (β=-0.20, 95% CI: -0.39, -0.02) percentiles (overweight risk), extending to more overweight percentiles (20th-50th) in the third follow-up (βs ranged from -0.28 until -0.26). Conclusion: Our results indicated the effectiveness of a practical lifestyle intervention to control rising trend of BMI at the onset of overweight and obesity in a middle-income population. These findings can be useful for planning obesity prevention programs in communities with similar socioeconomic statuses.